System Design, Development & Deployment Using Rapid By-Customer Demand With Business Principles Approach - Vista IV, Felipe P.; Chong, Kil To (Malaysian Journal of Computer Science, 2013)
We present a methodology employed to address the technical as well as business process needs in rapidly designing, developing and deploying systems. The system design methodology is composed of three major parts labeled as the executive decision, development and finals in which the concept of systems features analysis, business process criteria and delivery schedule as essential parts of the methodology is also presented. The proposed methodology is compared with existing formally defined methodologies though their principles, processes and practices. A marine information system that was developed using the proposed methodology is also presented to show the applicability and effectiveness of the proposed method.